Application of the Inquiry Learning Model to Improve the Critical Thinking Ability of Class X Ecosystem Material Students at MA Alkhairaat Bolangitang Barat - Bela Safira Mantang; Ramli Utina; Masra Latjompoh (Bioedukasi: Jurnal Pendidikan Biologi, 2024)
This research aims to improve students' critical thinking skills through an inquiry learning model on ecosystem material at MA Alkhairaat Bolangitang Barat. This research method is descriptive quantitative using a pre-experimental design type One Group Pretest-Posttest Design. Data were collected using observation sheets of inquiry learning implementation, student activity, and critical thinking indicator questions (tests).. The data analysis techniques used are the critical thinking ability and N-Gain categories. The average score before learning (Pre-test) was 25 and increased after implementing the inquiry learning model (Post-test) with an average score of 73. Apart from that, the normalization value of Gain was obtained from students' understanding of the Ecosystem material, reaching 0.63 with medium criteria. Based on the research results, it can be concluded that the inquiry learning model can improve students' critical thinking skills on ecosystem material. This can be seen from the results of the percentage of scores on the critical thinking ability indicator in the posttest scores which shows that the results of the students' posttest scores are higher than the pretest scores. This is because students are able to be actively involved and have the courage to ask questions and express opinions.